1999
DOI: 10.1016/s0022-0728(99)00318-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self-stress on the hydrogen absorption into palladium hydride electrodes of plate form under galvanostatic conditions

Abstract: Effects of diffusion induced stress on the hydrogen absorption into plate form electrodes of b-phase PdH x are discussed numerically based on the Volmer-Tafel route of the hydrogen evolution reaction, and thermodynamic considerations involving stress fields and non-ideal interactions of hydrogen in the electrode. It is found that the self-induced stresses enhance the absorption rate and may exceed the yield stress, especially when the thickness of the plate and/or charging current (or negative potential) incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…nH;0) has been canceled out by the boundary condition. This conclusion has also been proved by numerical simulation of hydrogen absorbing into a plate under galvanostatic charging [33]; it indicated that self-stress makes half-absorption time is less than the stress-free case although some details of the model di er from here. This could explain the fact ADCs increase with increasing nH and j0 (see Figs.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…nH;0) has been canceled out by the boundary condition. This conclusion has also been proved by numerical simulation of hydrogen absorbing into a plate under galvanostatic charging [33]; it indicated that self-stress makes half-absorption time is less than the stress-free case although some details of the model di er from here. This could explain the fact ADCs increase with increasing nH and j0 (see Figs.…”
Section: Discussionmentioning
confidence: 62%
“…The ÿrst one is the term u nH shown in Eq. (4) or (15), which accelerates the di usion process and makes ADCs greater than the SFDC [33,36]. Although the term nH is the local value of hydrogen content in solid, only the increment (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations